2014
DOI: 10.1111/poms.12215
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Supply Chains in Humanitarian Operations: Decentralization, Operational Mix, and Earmarked Funding

Abstract: T he work of international humanitarian organizations (IHOs) frequently involves operating in remote locations, decentralized decision-making, and the simultaneous implementation of development and disaster response programs. A large proportion of this work is funded by "earmarked" donations, since donors often exhibit a preference for the programs they are willing to fund. From extensive research involving qualitative descriptions and quantitative data, and applying system dynamics methodology, we model vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 31 publications
6
137
0
8
Order By: Relevance
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
See 2 more Smart Citations
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Other approaches include that of Kunz et al (2015), who concluded that UNHCR can save costs by centralising its fleet management programme; and that of Jahre and Heigh (2008), who found that a combination of postponement and strategic stocks significantly improves the speed, cost and quality of IFRC's response. Further, Aaki and Pedraza Martinez (2016) and Besiou et al (2014) showed that non-earmarked donations (postponement) improve operational performance; while Stauffer et al (2015) showed how temporary hubs (postponement) for their global fleet gives IFRC an opportunity to use of earmarked funding in a good way. These examples illustrate how combining different SCS may reduce certain risks without increasing others.…”
Section: Type Of Risk Reference Abnormalmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception is Nooraie and Parast (2016), who modeled the trade-off between increased investment in supply chain capabilities and reduced supply chain risks. Other examples are the studies of fleet management by Pedraza-Martinez et al (2011), Besiou et al (2014), andStauffer et al (2015). Further research could build on their approaches.…”
Section: A Proposed Research Agendamentioning
confidence: 99%
“…In general, it is challenging to get funds to support preparedness efforts as funding is commonly earmarked for specific operations (Van Wassenhove, 2006;Jahre and Heigh, 2008;Besiou et al 2014;Jahre et al 2016). Consequently, there is a need for an increased donor attention to preparedness efforts (Majewski, et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%